2018
DOI: 10.1002/tcr.201700083
|View full text |Cite
|
Sign up to set email alerts
|

Modified Synthesis Strategies for the Stabilization of low n TinO2n–1 Magnéli Phases

Abstract: Titanium reduced oxides TiO occupy, since long time, a prominent place on the landscape of binary metal oxides because of their intriguing ability to form extended defects that affect both the formation of new superlattices and different electronic behaviours. Related to these features, a wide range of practical applications has been achieved. Moved by the conviction of the great potential of understanding the influence of the reactivity, compositional variations and size effects on their functional properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In comparison, the doping of nonmetallic elements into traditional metal oxides is an effective method to form single-phase materials with optimized electrical conductivity. In addition, the introduction of extra oxygen vacancies is also helpful for the enhancement of LiPs adsorption. , Recently, the nonstoichiometric titanium oxides have attracted great attention in the field of energy storage and electrocatalysis because of their excellent electrical conductivity and periodic oxygen defect structure. In this material family, titanium monoxide (TiO) possesses the maximum reduction degree and highest theoretical electrical conductivity (∼4000 S·cm –1 at 298 K) . Similar to most of the metal oxides, TiO also possesses the characteristics of a polar surface, which is very suitable for the application as the sulfur hosts in Li–S batteries. However, the synthesis of TiO usually requires high-temperature calcination (>1100 °C) to facilitate the reduction of the TiO 2 precursor, which will lead to severe grain coarsening, leading to the difficulties in the morphology control.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the doping of nonmetallic elements into traditional metal oxides is an effective method to form single-phase materials with optimized electrical conductivity. In addition, the introduction of extra oxygen vacancies is also helpful for the enhancement of LiPs adsorption. , Recently, the nonstoichiometric titanium oxides have attracted great attention in the field of energy storage and electrocatalysis because of their excellent electrical conductivity and periodic oxygen defect structure. In this material family, titanium monoxide (TiO) possesses the maximum reduction degree and highest theoretical electrical conductivity (∼4000 S·cm –1 at 298 K) . Similar to most of the metal oxides, TiO also possesses the characteristics of a polar surface, which is very suitable for the application as the sulfur hosts in Li–S batteries. However, the synthesis of TiO usually requires high-temperature calcination (>1100 °C) to facilitate the reduction of the TiO 2 precursor, which will lead to severe grain coarsening, leading to the difficulties in the morphology control.…”
Section: Introductionmentioning
confidence: 99%
“…The shear vector [7] is clearly identified from the ( n –1) equally spaced spots between the origin and the strong reflections corresponding to (121) R , as shown in Figure 1(b–f), which is consistent with powder XRD results (Figure S1). High‐quality HR‐TEM images have been recorded for Ti 4 O 7 , [16,17] Ti 6 O 11 [18] and Ti 8 O 17 [17] . However, from the HR‐TEM images, specifying the Ti and O atoms including defects with atomic resolution in the regions near the CS planes remains challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows TEM images and EDS information for several systems of nano-TMO mentioned in the introduction section that can illustrate this. Figure 4a,b shows an example of reduced TiO 2 NPs, undoped and Mn-doped, prepared by a combination of sol-gel and carboreduction procedures [73,74]. The TEM study revealed that the particle size decreased when Mn was introduced (confirmed by EDS analysis) and, at the same time, a more faceted morphology was obtained.…”
Section: Basic Microstructural Characterization Of Tmos By Temmentioning
confidence: 94%